Terminologia prawosławna w rosyjsko-polskich słownikach ogólnych - Rygorowicz-Kuźma, Anna (Acta Polono-Ruthenica, 2018)
This article focuses on Orthodox terminology found in modern Russian-Polish general dictionaries: Wielki słownik rosyjsko-polski by A. Mirowicz, I. Dulewiczowa, I. Grek-Pabisowa, I. Martyniakowa and Wielki słownik rosyjsko-polski z kluczem polsko-rosyjskim edited by J. Wawrzyńczyk. The author shows the extent given lexicon is reflected in dictionaries, explores the ways of its translation and presents strengths and weaknesses of elaboration of entry articles. The analysis of translated equivalents also permits the identification of the main tendencies in Orthodox termino- logy in the Polish language.